Seroprevalence of Brucella spp. and Rift Valley fever virus infections in communal pastoral cattle at the wildlife-livestock interface, Zambezi region, Namibia - Madzingira, Oscar; Munzel, Hannah; Simasiku, Nicky Mowa; Lucas, Leo Tileni; Mwenda, Evelyn Nanjeke; Chinyoka, Simbarashe; Tjipura-Zaire, Georgina; Shilongo, Frieda; Borgemeister, Christian; Khaiseb, Siegfried; Chitanga, Simbarashe; Junglen, Sandra (Frontiers in Veterinary Science, 2024)
IntroductionBrucellosis and Rift Valley fever (RVF) are neglected zoonotic diseases (NZD) that threaten public health, animal health, and production in resource-limited countries including Namibia.MethodsThe objective of this cross-sectional study was to determine Brucella spp. and RVFV seroprevalence in cattle at the wildlife-livestock interface in the Kabbe South constituency (Zambezi region) of Namibia. Cattle sera (n = 371) were randomly collected from 18 cattle herds in six constituency areas and tested for antibodies against Brucella [complement fixation test (CFT) and indirect enzyme-linked immunosorbent (ELISA) assay in parallel] and Rift Valley fever virus (competitive ELISA).ResultsApparent individual animal prevalence for Brucella spp. was 5.9% (95% CI: 3.95%−8.81%, 22/371) and 20.8% (95% CI: 16.9%−25.2%, 77/371) based on the CFT and I-ELISA, respectively. For RVFV, apparent and true animal prevalence were 41.0% (95% CI: 36.1%−46.0%, 152/371) and 47.6% (95% CI: 41.8%−53.6%), respectively. Animal and true prevalence of Brucella spp. based on the CFT and ELISA in parallel were 22.6% (95% CI: 18.7%−27.2%, 84/371) and 19.7% (95% CI: 15.6%−24.4%), respectively. About 10.8% (40/371) of cattle tested positive for both Brucella spp. and RVFV antibodies. Prevalence of Brucella-positive cattle herds was 83.3% (15/18). Within herd Brucella spp. seroprevalence was 0%−70%. All cattle herds tested positive for RVFV, with prevalence of 1.7% to 70%. Binomial logistic regression revealed that sex was a significant predictor (p < 0.05) for RVFV seropositivity, but not for Brucella spp. seropositivity (p > 0.05). Test agreement between CFT and I-ELISA when used for the detection of anti-Brucella antibodies was poor (k = 0.2322).DiscussionBrucella spp. and RVFV infections were prevalent in communal pastoral cattle at the human-wildlife-livestock interface in the Zambezi region suggesting a higher likelihood of occurrence of reproduction losses in cattle and zoonotic disease in humans. We recommend the enforcement of the requirements for the vaccination of heifers against brucellosis in the affected communal areas to reduce the risk of human infection. The use of One Health principles for the surveillance, prevention and control of Brucella spp. and RVFV infections can promote the effective control of these zoonotic infections at the interface.